Pemanfaatan Instagram Sebagai Media Promosi Buku Amazing Iqra Balita Pada Akun @Iqrabalita.official - Rifqi Adli Pratama; Akhmad Syafrudin Syahri (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
Instagram is one of the social media platforms based on new media, social media Instagram is widely used by the Indonesian people as a media exchange of information, entertainment, education, even promotion. Iqra Balita is one of the businessmen who use Instagram as a media to promote his product. The research method used is qualitative descriptive method, where the author focuses on management activities, use picture, as well as observations of Iqra Balita in utilizing Instagram as a media promotion. The results of the findings of this research is, Iqra Balita in using instagram only as an intermediary media or media in providing information related to the product of amazing iqra balita book. The use of Instagram as a promotional media is very effective because of its simplicity, through the various features offered Iqra Balita is able to reach the target audience and also the target market. Even if Iqra Balita still use Instagram only as an intermediary in introducing their products through Instagram, then it requires a more interesting and interactive strategy or concept so that buyers are always satisfied with the products they use.